A commentary on the implications of medication prescription rights for the chiropractic profession. Issue 1 (December 2016) - Emary, Peter; Houweling, Taco; Wangler, Martin; Burnie, Stephen; Hood, Katherine; Erwin, W.
Abstract There is a growing desire within the chiropractic profession to expand the scope of practice to include limited medication prescription rights for the treatment of spine-related and other musculoskeletal conditions. Such prescribing rights have been successfully incorporated into a number of chiropractic jurisdictions worldwide. If limited to a musculoskeletal scope, medication prescription rights have the potential to change the present role of chiropractors within the healthcare system by paving the way for practitioners to become comprehensive specialists in the conservative management of spine / musculoskeletal disorders. However, if the chiropractic profession wishes to lobby to expand the scope of practice to include limited prescriptive authority, several issues must first be addressed. These would include changes to chiropractic education and legislation, as well as consideration of how such privileges could impact the chiropractic profession on a more theoretical basis. In this commentary, we examine the arguments in favour of and against limited medication prescription rights for chiropractors and discuss the implications of such privileges for the profession.